Condições antropométricas e metabólicas maternas e sua relação com a glicemia de recém-nascidos prematuros - Frizon , Bruna Juliana Zancanaro (2017)
Maternal nutritional, hormonal and metabolic status has direct implications on the development of the intrauterine infant and influence the child's health status throughout childhood and adulthood, an event defined as metabolic programming. Considering that preterm newborns (NBs) are more likely to develop several diseases throughout their life, the following questions arise: Are the maternal metabolic and anthropometric conditions determinant for the blood glucose (Glu) of the preterm newborn at birth and at six months of corrected age (6m CA)? The metabolic condition in mothers with preterm birth (PP) and their respective PTNB differ from mothers with term delivery (TA) and their respective term newborns (TNB)? Therefore, the objectives are: i) To establish whether there is a difference between maternal and infant metabolic status, between TNB and PTNB. ii) Identify whether the maternal metabolic and anthropometric status are correlated to the glycemic, lipidic and insulinemic profile in preterm birth and 6m CA. For that, a quantitative study of observational, longitudinal, prospective type was performed. The sample consisted of mothers and their respective PTNB who remained in the Neonatal Intensive Care Unit (NICU) of the Hospital Universitário do Oeste do Paraná (HUOP), which were compared to the control group, composed of newborns and their respective mothers. Anthropometric parameters (body weight, height and Body Mass Index (BMI) and biochemical plasma levels (Gli, triglycerides (TG), cholesterol (CT) and insulin (INS)) were evaluated. Maternal samples were collected between 24 and 48 hours after delivery and of the babies between 24 and 72 hours after, which was associated with a lower mean age, weight gain and BMI, accompanied by lower plasma levels of CT in relation to TNB mothers (p <0.05). PTNB presented higher Ins and Glu, accompanied by lower CT and TG at birth compared to TNB (p <0.05). At 6 months of CA only the TNB Glu remained higher than in TNB (p <0.05). Linear regression, it was demonstrated that body weight gain and maternal metabolism influenced the blood Glu of the preterm infants at birth and at 6m CA. While the greater maternal weight gain alone is related to lower blood glucose in the PTNB, the association of higher maternal weight gain with higher maternal Glu or TG results in increases in blood Glu in PTNB. At 6 m CA greater Glu or higher maternal TG are related to higher plasma Glu levels in PTNB suggesting that the maternal health condition at the time of delivery has effects on the Glu of premature at birth and early childhood. These findings reinforce the concept of metabolic programming by providing subsidies for new clinical behaviors and appropriate monitoring of pregnant and PTNB in order to avoid the installation of pathological conditions, especially diseases that break glycemic homeostasis, such as diabetes.